K-preintercalated MnO2 nanosheets as cathode for high-performance Zn-ion batteries - Li, Xiaomeng; Qu, Jiaqi; Xu, Junmin; Zhang, Sen; Wang, Xiaoxia; Wang, Xinchang; Dai, Shuge (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2021)
Manganese oxides are regarded as promising cathode materials for aqueous zinc ion batteries (ZIBs) due to their low cost and high theoretical capacity. However, their practical application is seriously hindered because of the inferior electronic conductivity, sluggish diffusion kinetics and structural instability. Herein, we develop a new K-preintercalated MnO2 (K0.19MnO2·0.56H2O, KMO) nanosheet by a facile hydrothermal method. Preintercalation of K+ ions into the MnO2 crystal layers with structural reconstruction can activate more active sites, strengthen the crystal structural stability and facilitate the insertion/extraction of Zn2+ ions. The charge shielding effect of crystal water promotes the diffusion kinetics of Zn2+ ions. The obtained KMO electrode delivers high specific capacity (107 mAh g−1) and good cycling stability (~87.5% capacity retention after 2000 cycles), revealing its potential application for aqueous ZIBs.